International Aid and Democracy Promotion Liberalization at the Margins - Tan, Bann Seng (Democratization Studies, 2021)
"International Aid and Democracy Promotion investigates the link between foreign aid and the promotion of democracy, using theory, statistical tests and illustrative case studies. This book challenges the field of development to recognize that democracy promotion is unlike other development goals. With a goal like economic development, the interests of the recipient and the donor coincide; whereas, with democratization, authoritarian recipients have strong reasons to oppose what donors seek. The different motivations of donors and recipients must be considered if democracy aid is to be effective. The author examines how donors exercise their leverage over aid recipients, and, more importantly, why, using selectorate theory to understand the incentives of both aid donors and recipients. International Aid and Democracy Promotion will be of great interest to academics and students of development and democratization, as well as policy makers with authority over foreign aid allocation. Open Access for this book is generously supported by the Ashoka University."